Application of the intramolecular asymmetric Stetter reaction to the synthesis of 2,3-, 2,4-, and 2,5- disubstituted cyclopentanones and the development of the azolium carbene catalyzed Wallach rearrangement with an application to the asymmetric synthesis of α-chloroesters - Reynolds, Nathan Thomas, author; Rovis, Tomislav, advisor; Elliott, C. Michael, committee member; Hegedus, Louis S., committee member; McNeil, Michael R., committee member; Strauss, Steven H., committee member (Colorado State University. Libraries, 2006)
A series of disubstituted cyclopentanones has been synthesized by the intramolecular Stetter reaction from racemic substrates containing one chiral center. 2,3- and 2,4-disubstituted cyclopentanones were synthesized as an approximately 1:1 mixture of cis- and trans-diastereomers with high enantioselectivity. The Stetter reaction of 2,5- disubstituted cyclopentanones proved to be substrate controlled, resulting in the selective formation of the cis-diastereomers with low enantiomeric excess. The conversion of α-haloaldehydes to α-reduced esters, the Wallach rearrangement, has been catalyzed by azolium carbenes. The scope of the reaction is broad allowing the transformation of a wide variety of α-haloaldehydes into the corresponding esters. Primary and secondary alcohols are efficient nucleophiles for this reaction and the acylation of aniline has been demonstrated. Evidence for the proposed in situ generated acyl azolium species was gained by the demonstration of the kinetic resolution of racemic-ethyl lactate and the desymmetrization of hydrobenzoin using a chiral triazolium salt. An asymmetric synthesis of α-chloroesters has been developed via an asymmetric protonation of the in situ generated chiral enolate. Treatment of α,α-dichloroaldehydes with a chiral triazolium salt in the presence of base and a nucleophilic alcohol provides the desired α-chloroesters in good yield. The reaction is applicable to the synthesis of phenyl and benzyl α-chloroesters with high enantiomeric excess, with other alcohols providing the desired product with lower enantiomeric excess. The product α-chloroesters are useful intermediates for the synthesis of more complex structures and the conversion of the products to α-chloroalcohols, α-chloroacids, and α-azido and α-thioesters has been demonstrated.
Keywords: organic chemistry